Prospective use of serial questionnaires to evaluate the therapeutic efficacy of 18F-fluorodeoxyglucose (FDG) positron emission tomography (PET) in suspected lung cancer. Issue 1 (1st January 2003) - Herder, G J; van Tinteren, H; Comans, E F; Hoekstra, O S; Teule, G J; Postmus, P E; Joshi, U; Smit, E F
Abstract : Background: A study was undertaken to study the effect of 18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET) on the diagnosis and management of clinically problematic patients with suspected non-small cell lung cancer (NSCLC). Methods: A prospective before-after study was performed in a cohort of all 164 patients (university/community settings) referred for PET between August 1997 and July 1999. PET was restricted to cases where non-invasive tests had failed to solve clinical problems. The impact on diagnostic understanding and management was assessed using questionnaires (intended treatment without PET, actual treatment choice after PET, post hoc clinical assessment). Results: Diagnostic problems especially pertained to unclear radiological findings (n=112; 63%), mediastinal staging (n=36; 20%), and distant staging issues (n=16; 9%). PET findings were validated by reviewing medical records. PET had a positive influence on diagnostic understanding in 84%. Improved diagnostic understanding solely based on PET was reported in 26%. According to referring physicians, PET resulted in beneficial change of treatment in 50%. Cancelled surgery was the most frequent change in treatment after PET (35%). Conclusion: FDG PET applied as "add on" technology in patients with these clinical problems appears to be a clinically useful tool, directly improving treatment choice in 25% of patients. The value of increased confidence induced by PET scanning requires further evaluation.